A fault diagnosis method for photovoltaic module current mismatch based on numerical analysis and statistics. (1st September 2021) - Zhang, Zhixiang; Ma, Mingyao; Wang, Hai; Wang, Haisong; Ma, Wenting; Zhang, Xing
Highlights: Online diagnosis of current mismatch faults of PV modules based on I-V curve. The characteristics of different types of current mismatch faults are studied. I-V features of current mismatch faults are explained with the reverse bias model. A method of I-V curve division and linear fitting is proposed to decouple mismatch. It is verified that the method has strong discriminative power and adaptability. Abstract: Photovoltaic (PV) module faults will not only reduce the power generation efficiency of PV modules, but also cause a series of safety problems. As the most common fault type, current mismatched fault leads to the decrease of the output current of the PV module resulting in a step in the I-V characteristic curves and multiple peaks in the P-V curves, such that the output power of the PV modules will be greatly affected. This paper focuses on current mismatched faults caused by partial shading, hot spot and crack through the investigation of faulty PV modules in actual PV power plants. The I-V characteristics of PV modules with current mismatch type faults are tested, and their fault characteristics are extracted. Not only can the current mismatch make the I-V characteristic curve of the module a step, but also the cause of the I-V curve of each current mismatched fault is analyzed in combination with the reverse bias model of the PV cell. In order to further decouple the features of different faults in the I-V curve step, a numerical analysis and statistical method is proposed for diagnosing PV module mismatch faults, which divides the I-V curve into a high voltage area and a low voltage area. The detection line composed of key points in the low voltage area is used to detect mismatch, while the current drop and linear regression fitting of the step data are used to identify the specific fault types in the high voltage area. Combined with the actual I-V data of PV modules under different working conditions, four case studies involving various types of faults are demonstrated to show that the proposed fault diagnostic method exhibits strong discriminating power and adaptability, and high practical application value.